2021 IEEE Global Humanitarian Technology Conference (GHTC) 2021
DOI: 10.1109/ghtc53159.2021.9612415
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Dead Zone: a Bottleneck in Humanitarian Ionospheric Radio Communications

Abstract: High Frequency (HF) radio communications are used in humanitarian work in areas where local networks are non-existent, or destroyed by natural disaster or human conflict. Direct point-to-point communications are realized over long distances, independent of local networks, using the ionosphere as a natural high-altitude reflector. HF ionospheric radio is essential for humanitarian organizations delivering basic healthcare in poor and remote areas. Normally, with proper frequency planning, ionospheric radio will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…(2012), Walden. ( 2016) §4.6 Witvliet et al (2014), Witvliet et al (2015c), Witvliet et al (2015a), Witvliet et al (2015b), Witvliet et al (2016b), Witvliet et al (2016a); Witvliet and Alsina-Pagès (2017); Witvliet et al (2019); Witvliet (2021); Witvliet et al (2023) Witvliet and Van Maannen (2005) Witvliet and Van Maannen (2006a) Witvliet and Van Maannen (2006b) Plasma Cutoff and Single-Mode Fading Perry et al (2018) Radio Propagation (General) Vanhamel et al (2022) Luetzelschwab et al (2022) §4.5 Serra (2022) Solar Eclipses Bamford. (2000) Frissell.…”
Section: Topicunclassified
See 1 more Smart Citation
“…(2012), Walden. ( 2016) §4.6 Witvliet et al (2014), Witvliet et al (2015c), Witvliet et al (2015a), Witvliet et al (2015b), Witvliet et al (2016b), Witvliet et al (2016a); Witvliet and Alsina-Pagès (2017); Witvliet et al (2019); Witvliet (2021); Witvliet et al (2023) Witvliet and Van Maannen (2005) Witvliet and Van Maannen (2006a) Witvliet and Van Maannen (2006b) Plasma Cutoff and Single-Mode Fading Perry et al (2018) Radio Propagation (General) Vanhamel et al (2022) Luetzelschwab et al (2022) §4.5 Serra (2022) Solar Eclipses Bamford. (2000) Frissell.…”
Section: Topicunclassified
“…To support work from humanitarian organizations that deliver basic healthcare in low and middle income countries (LMIC), such as Médecins sans Frontières, a group consisting of radio amateurs and scientists established the optimum NVIS antenna height through simulation and measurement (Witvliet and Van Maannen 2005;Witvliet and Van Maannen 2006a;Witvliet and Van Maannen 2006b;Witvliet et al, 2015a). It was shown that the use of mobile whip antennas will result in a Dead Zone between 30 and 60 km of the transmitter due to suppression of high-angle waves (Witvliet, 2021).…”
Section: Near Vertical Incidence Skywave Propagationmentioning
confidence: 99%